STUDENTS' ENTHUSIASM FOR INVESTING IN THE SHARIA CAPITAL MARKET REMAINS LIMITED - Nainggolan, Edisah Putra (Proceeding International Seminar of Islamic Studies, 2024)
Investing with Islamic principles is the worship of Allah. In its teachings, Islam aims to achieve inner and outer happiness in this world and the afterlife for both the present and future generations. The Sharia capital market applies Sharia principles in economic transaction activities and is free from prohibited things such as usury, gambling, and speculation. This research aims to analyze factors in students' low interest in investing in the Islamic capital market. The factors that influence this include financial literacy, capital, and also risk. The population in this study were final semester students at Islamic Universities in Medan City with a sample of 100 people chosen randomly. The data analysis technique uses Structural Equation Modelling (SEM). The research results show that financial literacy has a significant influence on students' low interest in investing, capital has a significant influence on students' low interest in investing and risk also influences students' low interest in investing